2016
DOI: 10.1002/ece3.2472
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of provenance to soil quality enhanced stress reaction of young beech trees to summer drought

Abstract: Climate projections propose that drought stress will become challenging for establishing trees. The magnitude of stress is dependent on tree species, provenance, and most likely also highly influenced by soil quality. European Beech (Fagus sylvatica) is of major ecological and economical importance in Central European forests. The species has an especially wide physiological and ecological amplitude enabling growth under various soil conditions within its distribution area in Central Europe. We studied the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 61 publications
(99 reference statements)
0
3
1
Order By: Relevance
“…Our findings of only limited acclimation contrast with dendrochronological results from larger (continent-wide) studies which found a lower drought sensitivity of mature beech trees in dry-marginal beech populations as compared to more mesic central populations, pointing at successful drought adaptation of these genetically more distant populations [67][68][69]. Similarly, many common garden experiments with beech seedlings and saplings of different European origins revealed a higher drought resistance and/or faster drought recovery of populations from drier and warmer sites [9,70,71], which seems to contrast with our results. That the beech populations of the drier sites of our study were not successful in maintaining growth under increasingly stressful climatic conditions might be a consequence of the relatively small genetic distances found between our populations [53] and perhaps insufficient genetic adaptation to the rapid climate aridification in recent time.…”
Section: The Climate Change Acclimation and Adaptation Potential Of B...contrasting
confidence: 82%
“…Our findings of only limited acclimation contrast with dendrochronological results from larger (continent-wide) studies which found a lower drought sensitivity of mature beech trees in dry-marginal beech populations as compared to more mesic central populations, pointing at successful drought adaptation of these genetically more distant populations [67][68][69]. Similarly, many common garden experiments with beech seedlings and saplings of different European origins revealed a higher drought resistance and/or faster drought recovery of populations from drier and warmer sites [9,70,71], which seems to contrast with our results. That the beech populations of the drier sites of our study were not successful in maintaining growth under increasingly stressful climatic conditions might be a consequence of the relatively small genetic distances found between our populations [53] and perhaps insufficient genetic adaptation to the rapid climate aridification in recent time.…”
Section: The Climate Change Acclimation and Adaptation Potential Of B...contrasting
confidence: 82%
“…Our results seem to contradict studies that indicated a lower drought sensitivity of beech in dry‐marginal southern populations, where local drought adaptation in these genetically more distant populations is likely (Cavin & Jump, 2017; Magri et al, 2006; Muffler et al, 2020). In fact, many common garden drought experiments with beech seedlings and saplings of different provenances demonstrate that populations originating from drier sites in most cases showed signs of higher drought tolerance and/or faster recovery from drought stress than moister origins (Buhk et al, 2016; Leuschner, 2020; Thiel et al, 2014). Overall, population differentiation was apparently more often described in morphological, phenological and growth‐related traits (such as leaf size and thickness) than in physiological properties (as embolism resistance) (Frank et al, 2017; García‐Plazaola & Becerril, 2000; Knutzen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Intra-specific gradients of beech are commonly available in the literature (Stojnić et al 2017;Cocozza et al 2016;Bolte et al 2016;Ježík et al 2016;Buhk et al 2016;Harter et al 2015). However, the majority of them focus on the southern, western, and/or northern margins of beech distribution range.…”
Section: Genetic Effect In Beech Populationsmentioning
confidence: 99%